Construction of three coordination polymers based on tetranuclear copper(ii) clusters: syntheses, structures and photocatalytic properties. Issue 14 (17th March 2016) - Liu, Lu; Peng, Yan-Fen; Lv, Xiu-Xiu; Li, Ke; Li, Bao-Long; Wu, Bing
Abstract : Three coordination polymers based on the tetranuclear copper(ii ) cluster [Cu4 (μ3 -OH)2 ] were synthesized by the hydrothermal reaction. They are universal high efficient photocatalysts for the degradation of the organic dyes. Abstract : Three intriguing metal-cluster based coordination polymers (MCOFs) {[Cu4 (OH)2 (itp)2 (btc)2 (H2 O)4 ][Cu(H2 O)4 (Hbtc)]2 ·4H2 O} n (1 ), {[Cu4 (OH)2 (itp)2 (btc)2 ]·2EtOH·2H2 O} n (2 ) and {[Cu4 (OH)2 (itp)2 (sip)2 (H2 O)4 ]·4H2 O} n (3 ) were synthesized by the reaction of 1-imidazol-1-yl-3-(1, 2, 4-triazol-4-yl)propane (itp), 1, 3, 5-benzenetricarboxylate (btc) or 5-sulfoisophthalate (sip) and CuCl2 using a hydrothermal method.1 consists of an unprecedented (3, 4)-connected 2D network based on the tetranuclear copper(ii ) clusters [Cu4 (μ3 -OH)2 ] and Cu1 cores with a Schläfli symbol of (6 2 ·8)2 (6·8 4 ·10) and an unprecedented 2D → 3D polythreaded motif.2 shows an unusual (3, 10)-connected 3D network based on the tetranuclear copper(ii ) cluster [Cu4 (μ3 -OH)2 ] with the Schläfli symbol of (3·4·5)2 (3 4 ·4 6 ·5 10 ·6 15 ·7 10 ).3 exhibits a 2D (4, 4) network based on tetranuclear copper(ii ) clusters [Cu4 (μ3 -OH)2 ].1 –3 are semiconducting in nature, with E g of 2.29 eV (1 ), 2.27 eV (2 ) and 2.39 eV (3 ).1–3 are universal and highly efficient photocatalysts for the degradation of organic dyes such as methyl orange (MO), methylene blue (MB) and rhodamine B (RhB) under UV irradiation, are very stable and easily separated from the reaction system for reuse.